Constructions of type "leat jođus", "leat johtimin" in North Saami and Inari Saami subcorpuses of SIKOR - Kuokkala, Juha (Zenodo, 2022)
This data set contains the occurrences of constructions of types leat jođus , leat johtimin in North Saami and leđe joođoost , leđe jotemin in Inari Saami, extracted from the SIKOR korpus. The data is processed so that infinitive, illative and comitative complements of the construction have been marked out (based on original automated analysis of the corpus and corrected manually). The data is further analyzed in a paper published in Journal de la Société Finno-Ougrienne 98: https://doi.org/10.33340/susa.97223 .